Methodology for Evaluating Price-Quota Curves Used by Price-Maker Generation Companies in Pool-Based Electricity Market - Cabana, Tiago Gomes [UNESP]; Nepomuceno, Leonardo [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2023)
In energy markets, self-scheduling is a central problem solved by a Generation Company (GENCO) for achieving its goal of profit maximization. This problem consists in calculating the generation dispatch of the units belonging to the company that maximizes its profit in the day-ahead pool electricity market. The self-scheduling models generally use a price-quota curve as input data. This curve estimates the market clearing price for each quota that a price-maker GENCO generates in this market. Price-quota curves are crucial for a reliable calculation of the company's profit. Recently, some innovative methods for building this curve have been proposed, however a methodology for evaluating the ability of such curves to estimate market clearing prices and profits has been very sparsely discussed in the literature. This paper proposes a methodology for evaluating price-quota curves which is based on the simulation of the basic steps of the decision making process that the company takes for calculating its strategic offer blocks. Results show that the proposed methodology is able to identify the best price-quota curves, in what regards its ability to estimate prices and profits.
Keywords: Electricity Markets; Price-Quota Curve; Self-Scheduling Model; Thermal Units